Grupos de mútua ajuda para familiares de dependentes químicos: ritos e mitos no bailes da sombras - Caldas, Sandra Regina Martins (2017)
This study aims to assess the Nar-Anon anonymous mutual-aid family groups of drug addicts based on reviews from interviewees experiences with members of this brotherhood in the city of São Paulo. What values are incorporated by its members? How do such groups achieve their primary goal of providing support to addicts’ family members? This research was conducted based on the use of semi-structured interviews as well as a bibliographic study on the structure of these groups, an ethnographic analysis on the experience within the Nar-Anon groups considering the material collected through the interviews alongside the researcher's own experience over eight years of attendance in two rooms of the brotherhood in the city, between 2008 and 2016.Therefore, emphasis is placed on the sense attributed by the group to recovery and spirituality for the construction of a new way of live coexisting with the chemical dependency syndrome. The approach adopted here will be that of Magnani, for whom looking close up and within (2002) allows one the apprehension of behaviors and meanings, for that matter, turning to a look from outside and from a distance for a broadened understanding of these groups as a totality. Authors like Foucault, Le Breton, Goffman, Novaes, and Campbell provide a critical view on the collected material